Switching defence for switched systems under malicious attacks: A Stackelberg game approach. (November 2021) - Huang, Yabing; Zhao, Jun
Abstract: The security issue of switched systems is researched from a noncooperative dynamic game-theoretic perspective in this paper. A Stackelberg game is developed for the switched autonomous system suffering malicious attacks, and the Stackelberg equilibrium switching and attack strategies are constructed respectively. Afterwards, the proposed game-theoretic approach is extended to switched control systems. A Stackelberg Nash game is consequently established to characterize the hierarchical decision making processes, where the controller and the attacker are the followers who simultaneously make their own decisions, and a sufficient condition is provided for the construction of the Stackelberg Nash equilibrium. Finally, a continuous stirred tank reactor is exploited to validate the effectiveness and applicability of the proposed results.